Wideband RCS Reduction of Microstrip Array Antenna Based on Absorptive Frequency Selective Surface and Microstrip Resonators - Jingjing Xue; Wen Jiang; Shuxi Gong (International Journal of Antennas and Propagation)
An approach for wideband radar cross section (RCS) reduction of a microstrip array antenna is presented and discussed. The scheme is based on the microstrip resonators and absorptive frequency selective surface (AFSS) with a wideband absorptive property over the low band 1.9–7.5 GHz and a transmission characteristic at high frequency 11.05 GHz. The AFSS is designed to realize the out-of-band RCS reduction and preserve the radiation performance simultaneously, and it is placed above the antenna with the operating frequency of 11.05 GHz. Moreover, the microstrip resonators are loaded to obtain the in-band RCS reduction. As a result, a significant RCS reduction from 1.5 GHz to 13 GHz for both types of polarization has been accomplished. Compared with the reference antenna, the simulated results exhibit that the monostatic RCS of the proposed array antenna in x- and y-polarization can be reduced as much as 17.6 dB and 21.5 dB, respectively. And the measured results agree well with the simulated ones.